“Loro parlano da sole”. Silenzio, dialogo e polifonia in “Una donna sola” di Franca Rame come forma di querelle des femmes - Arriaga Florez, Mercedes (Studia Romanica Posnaniensia, 2018)
The protagonist of “Una donna sola” is a housewife who keeps a monologue with herself and with several invisible people outside the stage. As the plot develops different types of dialogic relationships and verbal interactions are introduced in the story. The protagonist, through her mono-dialogue, moves from a state of unconsciousness to one of awareness, from a passive victim to an active subject. Her character is the “crazy” woman who shows uncomfortable truths. The deliberate staging of the subordinate role of women becomes a form of Querelle. On the one hand Franca Rame denounces violence and male authoritarianism, on the other hand she proposes the deconstruction and reconstruction of female identities.